2018
DOI: 10.1101/406355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An antigenic atlas of HIV-1 escape from broadly neutralizing antibodies

Abstract: Anti-HIV broadly neutralizing antibodies (bnAbs) have revealed vaccine targets on the virus's Env protein and are themselves promising immunotherapeutics. The efficacy of bnAb-based therapies and vaccines depends in part on how readily the virus can escape neutralization. While structural studies can define contacts between bnAbs and Env, only functional studies can define mutations that confer escape. Here we map how all single amino-acid mutations to Env affect neutralization of HIV by nine bnAbs targeting f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Conversely, there were instances where previous studies had defined sites on Env with close proximity and hydrogen bonding to the antibody by X-ray crystallography, such as residues 595 to 609 for F240 19 , but we did not observe strong negative selection taking place at sites 595, 596, or 605 -609. Other studies have demonstrated that side chain proximity does not necessarily predict the contribution of a site to the formation of a protein-protein complex [25][26][27][28][29][30][31][32] , and this case with F240 further illustrates how analysis by Phage-DMS can yield information on the critical binding interactions of an antibody distinct from the identity of interfacing sites obtained by structural studies.…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, there were instances where previous studies had defined sites on Env with close proximity and hydrogen bonding to the antibody by X-ray crystallography, such as residues 595 to 609 for F240 19 , but we did not observe strong negative selection taking place at sites 595, 596, or 605 -609. Other studies have demonstrated that side chain proximity does not necessarily predict the contribution of a site to the formation of a protein-protein complex [25][26][27][28][29][30][31][32] , and this case with F240 further illustrates how analysis by Phage-DMS can yield information on the critical binding interactions of an antibody distinct from the identity of interfacing sites obtained by structural studies.…”
Section: Discussionmentioning
confidence: 87%
“…Antibodies that target conserved structures on the HIV-1 Env generally impart broad and potent nAb responses (47). Changes at specific amino acid sites that affect this conserved structure account for escape from bnAbs.…”
Section: Env Mutations Are Present At Different Frequenciesmentioning
confidence: 99%
“…To identify resistance mutations, we incubated the mutant virus libraries with or without enfuvirtide, infected cells, and then identified the mutant viruses that were enriched upon drug selection using deep sequencing. This approach is similar to the mutational antigenic profiling process we have previously used to map antibody escape [10,11]. Briefly, 5×10 5 to 1×10 6 infectious units of three independent mutant virus libraries were incubated in the presence of 8ug/mL of enfuvirtide, then infected into 1×10 6 SupT1.CCR5 cells in R10 (RPMI with 10% FBS, 1% 200 mM L-glutamine, and 100 units/mL of penicillin and streptomycin), containing 100ug/mL DEAE-dextran.…”
Section: Resistance Profilingmentioning
confidence: 99%
“…Selected and mock-selected viral cDNA was then sequenced with a barcoded subamplicon sequencing approach as previously described [8], which introduces unique molecular identifiers used to correct sequencing errors. The amount of virus library that entered cells was quantified via qPCR [11].…”
Section: Resistance Profilingmentioning
confidence: 99%